Hepatitis B virus-specific effector CD8+ T cells are an important determinant of disease prognosis: A meta-analysis. Issue 18 (24th April 2019) - Zheng, Juzeng; Ou, Zhanfan; Xu, Yilun; Xia, Ziqiang; Lin, Xianfan; Jin, Sisi; Liu, Yang; Wu, Jinming
Highlights: Acute hepatitis B patients have higher specific CD8 + T cells level than CHB patients. Specific CD8 + T cells level is negatively correlate to HBV DNA level. Specific CD8 + T cells level is negatively correlate to HBeAg level. Specific CD8 + T cells have no significant correlation to serum ALT level. Abstract: Background: Hepatitis B virus (HBV)-specific effector CD8 + T cells are critical for viral clearance. To determine the effects of HBV-specific effector CD8 + T cells on HBV infection, we performed a meta-analysis of the available literature. Methods: Electronic database searches identified appropriately designed studies that detected specific CD8 + T cells in HBV-infected patients. Our main endpoints were the course of infection, seroconversion of HBV "e" antigen (HBeAg), the level of HBVDNA, and alanine aminotransferase (ALT) activity. We used a fixed/random model for analysis, according to the results of a heterogeneity test (P value of Q-squared, I 2 ). Results: Our searches found five eligible articles. Pooled estimation of the reported results showed that levels of specific CD8 + T cells were significantly higher in patients with acute hepatitis B than in patients with chronic hepatitis B (odds ratio [OR] = 76.30, 95% confidence interval [CI]: 15.37–378.70). With respect to chronic hepatitis B, patients with <10 7 copies/ml HBVDNA had higher levels of specific CD8 + T cells relative to patients with >10 7 copies/ml HBVDNA, but the difference had no statistics significance (OR: 3.89, 95% CI: 0.71–21.33). Patients with negative HBeAg or positive anti-HBeAg antibody (anti-HBe) results had significantly higher levels of specific CD8 + T cells versus patients with positive HBeAg results (OR: 5.82, 95% CI: 1.41–24.13). There were no significant associations between the levels of specific CD8 + T cells and serum ALT activity (OR = 0.86, 95% CI: 0.01–74.15). Conclusion: HBV-specific effector CD8 + T cells influence the disease activity in HBV-infected patients in various ways and determine prognosis by eliminating the virus. Therefore, efforts of studying HBV-specific effector CD8 + T cells focused vaccine are potentially needed.